Bilateral inter-arm coordination in freestyle swimming: Effect of skill level and swimming speed - Nikodelis, T.; Kollias, I.; Hatzitaki, V. (Journal of Sports Sciences, 2005)
The aim of this study was to examine the influence of level of skill and swimming speed on inter-limb coordination of freestyle swimming movements. Five elite (2 males, 3 females; age 18.9±1.0 years, height 1.71±0.04m, body mass 62.1±?7.0kg) and seven novice (age 22.0?±?2.0 years, height 1.77±0.04m, body mass 74.8±9.0kg) swimmers swam a sprint and a self-paced 25m freestyle trial. The swimming trials were recorded by four digital cameras operating at 50 Hz. The digitized frames underwent a three-dimensional direct linear transformation to yield the three-dimensional endpoint kinematic trajectories. The spatio-temporal relationship between the upper limbs was quantified by means of the peak amplitude and time lag of the cross-correlation function between the right and left arm's endpoint trajectories. A strong anti-phase coupling between the two arms, as confirmed by peak amplitudes greater than 0.8, was noted for both groups and swimming speeds. Significantly higher (P ?<0.05) peak amplitudes were observed for the sprint compared with self-paced swimming. No significant differences in the strength of inter-limb coupling were noted between the elite and novice swimmers (P >0.05). Time lags were very close to 0ms and did not differ between groups or swimming speeds. We conclude that in freestyle swimming, the intrinsic anti-phase (180° phase difference) inter-limb relationship is strongly preserved despite the physically powerful environmental influence of the water and this "preferred" pattern is not affected by level of skill. In contrast, increasing movement speed results in stronger inter-limb coupling that is closer to the anti-phase inter-limb relationship.